SMLocalizer, a GPU accelerated ImageJ plugin for single molecule localization microscopy - Bernhem, Kristoffer (Bioinformatics, 2018)
SUMMARY: SMLocalizer combines the availability of ImageJ with the power of GPU processing for fast and accurate analysis of single molecule localization microscopy data. Analysis of 2D and 3D data in multiple channels is supported. AVAILABILITY AND IMPLEMENTATION: Plugin freely available for Fiji and ImageJ2.0 through https://sourceforge.net/projects/smlocalizer/. Plugin also available for continuous updates through ImageJ update system, add http://sites.imagej.net/Cellular-Biophysics-KTH/ as update site in ImageJ. Java and CUDA source code freely available on the web at https://github.com/KristofferBernhem/SMlocalizer. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.